A cationic surfactant assisted selective etching strategy to hollow mesoporous silica spheres - Fang, Xiaoliang; Chen, Cheng; Liu, Zhaohui; Liu, Pengxin; Zheng, Nanfeng (Nanoscale, 2011)
Hollow mesoporous silica spheres have recently attracted increasing attention. However, effective synthesis of uniform hollow mesoporous spheres with controllable well-defined pore structures for fundamental research and practical applications has remained a significant challenge. In this work, a straightforward and effective "cationic surfactant assisted selective etching" synthetic strategy was developed for the preparation of high-quality hollow mesoporous silica spheres with either wormhole-like or oriented mesoporous shell. The as-prepared hollow mesoporous silica spheres have large surface area, high pore volume, and controllable structure parameters. Our experiments demonstrated that cationic surfactant plays critical roles in forming the hollow mesoporous structure. A formation mechanism involving the etching of solid SiO(2) accelerated by cationic surfactant followed by the redeposition of dissolved silica species directed by cationic surfactant is proposed. Furthermore, the strategy can be extended as a general strategy to transform silica-coated composite materials into yolk-shell structures with either wormhole-like or oriented mesoporous shell.